Bichronous scientific writing course for medical faculty during Covid-19: a SWOT analysis experience - Khojasteh, Laleh; Zarifsanaiey, Nahid; Karimian, Zahra (Frontiers in Education, 2024)
After the COVID-19 pandemic, Shiraz University of Medical Sciences failed to deliver distant education to its largely foreign students since many of its faculty lacked the language abilities to create English e-contents and communicate with them. After numerous medical faculty English programs were canceled, we redesigned scientific writing courses using bichronous (asynchronous and synchronous) teaching. After forming a team, we performed a SWOT (strengths, weaknesses, opportunities, and threats) study of the medical faculty's present programs and proposed alternatives to prior course issues. In this interventional study fifty-nine eligible medical educators selected by purposeful sampling underwent a two and a half months bichronous scientific writing course from March to August 2021. The perspectives of the participants were evaluated through a SWOT analysis. Data were collected through online semi-structured interviews, and data collection continued until data saturation was achieved (40 participants). Data were then coded and analyzed based on conventional qualitative content analysis principles. Our planned blending sequence and e-feedback increased medical faculty's drive to learn, selfconfidence, and autonomy while improving their writing skills. Poor ICT and network infrastructure hindered course adoption. Due to the course's time and the faculty's own online teaching, many battled with computer vision syndrome, self-discipline, and distractions. Given the faculty's demanding professional lives, this designed course provided a learning opportunity for many that would not have been feasible otherwise. Our participants struggled with self-discipline and distractions, so setting a daily time limit may help them concentrate.